A Psychological Literary Approach to the First-Person Narrative Perspective in The Broken Wings - Na’in, Rizky Nabil Setyawan (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze the psychological aspects of the main character who uses a first-person point of view in the novel الأجنحة المتكسرة (The Broken Wings) by Khalil Gibran. The novel explores the inner experiences of the “I” character as he faces love, loss, and social pressure that shape his psychological condition. This research employs a literary psychology approach with a descriptive qualitative method. The primary data source is the novel الأجنحة المتكسرة. The data collection techniques include library research and note-taking during reading. In contrast, data analysis involves identifying, classifying, and interpreting expressions that reflect the psychological condition of the main character. The results show that the novel’s first-person point of view strengthens the depiction of inner conflict, deep feelings of love and suffering, and the emotional struggle of the main character. Through the literary psychology approach, it is found that the experience of unfulfilled love creates psychological pressure, sadness, and a process of self-maturation within the “I” character. Therefore, the use of the first-person point of view plays an important role in revealing the intensity of the character’s psychological experience in a deeper and more personal way.